Effect of juvenile idiopathic arthritis on facial skeleton morphology – literature review - Małyszko, Małgorzata; Szarmach, Izabela; Szarmach, Iga (Journal of Stomatology, 2015)
Introduction. Juvenile idiopathic arthritis (JIA) occurs in the developmental period and comprises a few pathological syndromes of unknown etiology and differentiated clinical picture. Seven types of JIA have been distinguished, with chronic arthritis as a common feature. The pathological process in the temporomandibular joint (TMJ) can be unilateral or bilateral, leading to severe growth disorders of the facial skeleton. Aim of the study. To review literature on facial skeleton morphology in patients suffering from JIA. Material and methods. Material for analysis consisted of literature data obtained from medical database of “MEDLINE”, “SCOPUS” and „WEB OF SCIENCE” published between January 1970 and February 2015. The key words that were used included: “juvenile idiopathic arthritis”, “juvenile chronic arthritis”, “juvenile rheumatoid arthritis” in association with such terms as “dentoskeletal morphology”, “dentofacial growth”, “craniofacial development”, “cephalometric analysis”, “cephalometry”, in various combinations. Inclusion and exclusion criteria were defined to assess the article’s relevance. Publications in the Polish and English language were taken into consideration. Results. Fourteen articles meeting the established inclusion criteria were qualified for review. Homogeneity of the respective research papers was assessed to verify the possibility of defining the common denominator of study results. Chosen cephalometric parameters of 652 JIA patients aged 2.17-44.4 years were compared to the control group. Conclusion. Chronic inflammation of the TMJ is an important issue, especially in growing patients. It is likely to cause characteristic growth anomalies in the facial skeleton, such as microgenia, retrognathia, skeletal open bite or increased facial convexity, especially when the TMJ inflammation is bilateral. Further long-term studies are necessary to compare the growth of the mandible and the whole complex of the facial skeleton in patients with and without TMJ inflammation in the respective types of the disease.